ISSUES OF COMPATIBILITY HUMAN RIGHTS AND ISLAM: The Experience of Egypt and Indonesia (State Islamic University (UIN) of Sunan Ampel Surabaya, 2007)
This paper describes the plurality of Muslim responses to the modern conception of human rights, drawing in particular on Muslim interpretations of key human rights issues in the discourse of human rights and Islam -women’s rights, religious freedom and minority rights, and corporal punishment- in Egypt and Indonesia. The case studies of Egypt and Indonesia point to wide range of responses among Muslims to these issues, but also suggest that Islam is not incompatible with the modern conception of human rights. This paper argues that on the issues of human rights, Muslims do not share a single, monolithic stance. Instead, there is a variety of arguments based on various Islamic schools of thought and Islamic religious groups. As a result, the issues of human rights and their implementation have elicited a wide range of responses among Muslims.